Digital Nomadism: Remote Work Practices and Emerging Forms of Entrepreneurship - Muhammad Asif Khan; Ahmad Syamil; Junaid Ali Saeed Rana; Rino Subekti; Noor ul Amin (Gadjah Mada International Journal of Business, 2026)
Digital nomadism has become a novel work style, transforming the global economy and jobs while providing entrepreneurial avenues for profit in a rapidly emerging digital economy. Digital nomadism promotes a new way of life that changes cultural attitudes towards and practices of traditional business; that is, workers are using technologies to facilitate remote work from anywhere in the world, even in traveling, rather than being fixed in one office. This mixed-method, exploratory research project investigates the emergence of digital nomadism and how it is redefining entrepreneurship through two inter-related studies: Study 1 focuses on the use of text mining, sentiment analysis, and social network modeling on a broad data layer; Study 2 includes 75 surveys and 28 interviews with entrepreneurs and freelancers about their observations and experiences. The results of this study show that digital nomadism is clustering around internet hubs, such as Southeast Asia, Eastern Europe, and Central locations in Latin America. The operations of digital nomad entrepreneurs and freelancers cluster around major themes such as freelance contracting, start-ups, selling online courses, co-working spaces, and lifestyle travel, all in industries founded on flexibility, creativity, innovation, or technology, education, sustainability, and networking